Effects of psychosocial interventions on wellbeing in individuals with severe mental illness: a systematic review - Johansson, David; Skillmark, Mikael; Allgurin, Monika (Frontiers in Psychology, 2025)
IntroductionWellbeing, encompassing hedonic and/or eudaimonic components, provides a two-dimensional framework for evaluating the effects of psychosocial interventions for individuals with severe mental illness (SMI). This study investigates how this conceptualization of wellbeing is reflected in existing research on psychosocial interventions for people with SMI. This is the first systematic review to assess the effects of psychosocial interventions on wellbeing as a purely positive phenomenon in this population. The study was registered in PROSPERO (CRD42024598954).MethodA systematic review was conducted on intervention studies involving adults with SMI receiving psychosocial interventions in an out-patient setting, with a control condition and a wellbeing outcome aligned with a wellbeing framework. Five databases were searched, supplemented by manual searches, yielding 2,842 potential studies. Due to considerable heterogeneity (I2 = 94%), interventions were analyzed independently, with results summarized based on the proportion of studies reporting significant effects. The study followed PRISMA guidelines.ResultsSeventeen studies met the inclusion criteria. Only one study (6%) provided a full rationale for using a wellbeing measure as the primary outcome. Over 70% reported a significant positive effect on wellbeing. In 13 studies effect size could be calculated, 29% in reference to all 17 studies demonstrated a positive effect (ranging from small to large). Clinical implications of the wellbeing construct were discussed in 47% of the studies, including an increased emphasis on positive functioning. Fewer than 50% received a high-quality rating, and only three studies reporting significant effects used Intention-To-Treat (ITT) data.ConclusionResearch on two-dimensional wellbeing is a promising yet underprioritized field, providing a renewed focus on abilities and generating significant clinical implications. Wellbeing ought to be a prioritized outcome in out-patient treatment policies, but today no recommendation as to which interventions are most effective are possible due to insufficient data. The implications of detecting changes in wellbeing in individuals with SMI, along with recommendations for future research, are discussed.